(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
Intergenerational Learning in Indigenous Textile Communities of Practice was an interdisciplinary arts- and community-based study that inquired into the intergenerational practices of beading and weaving in two Indigenous contexts – one in Southern Chile and the other in Northern Saskatchewan, Canada. The research process involved building relational networks, developing decolonizing methodologies, and working with collaborators, elders, community coordinators, and members of Indigenous textile communities of practice. The research methods, which are a focus of this article, included the use of artifacts to draw out memories and stories of intergenerational learning and to engage the communities in deciding how to share the knowledge generated. Both the data gathering methods and the knowledge mobilization led to arts-based outcomes. The study specifically inquired into how learning is structured and passed on to subsequent generations within communities of practice and the findings provide insights into the way this knowledge is transferred and/or disrupted. Critical reflection on the process highlighted some of the challenges that arose – both with the academic researcher and the community and inside the community.